If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6.50(10) + 2x = 4(x + 10) Multiply 6.50 * 10 65 + 2x = 4(x + 10) Reorder the terms: 65 + 2x = 4(10 + x) 65 + 2x = (10 * 4 + x * 4) 65 + 2x = (40 + 4x) Solving 65 + 2x = 40 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 65 + 2x + -4x = 40 + 4x + -4x Combine like terms: 2x + -4x = -2x 65 + -2x = 40 + 4x + -4x Combine like terms: 4x + -4x = 0 65 + -2x = 40 + 0 65 + -2x = 40 Add '-65' to each side of the equation. 65 + -65 + -2x = 40 + -65 Combine like terms: 65 + -65 = 0 0 + -2x = 40 + -65 -2x = 40 + -65 Combine like terms: 40 + -65 = -25 -2x = -25 Divide each side by '-2'. x = 12.5 Simplifying x = 12.5
| 10(a-6)=-25 | | 6(2x+5)+12= | | -3x-7-5=5x-2(2x+2) | | 2(7x+1)+11x= | | Graphx+3y=300 | | 0=x^4-36 | | (2x-11)+11= | | y=x^4-36 | | -60+5x=-4x+66 | | 5(x+7)-2x=3(2x+5)-1 | | 3xy-y+3x=1008 | | e^3x-4=7 | | 1.5=.75 | | 4p+8-3p=33 | | 1/2+3/8(-4)= | | 1/2+3/8(-5)= | | -11+2x=x+19 | | =3.45 | | 1/2+3/8(-6)= | | 4(x-6)+13(x+8)= | | 4x-35=9x | | 4x+7=Q | | 3(4-3x)=-6 | | 5+2(3-7)=3(2+5)-24 | | 4(4)-7= | | 20-8+3n-3=20 | | -8-7x=-6x+14 | | 4(3)-7= | | x^2=13/24 | | 4(2)-7= | | 11x+1=6x-5 | | 0-5y=20 |